Structural modifications of lanthanum silicate oxyapatite exposed to high water pressure. Issue 5 (May 2017) - Pons, Aénor; Béchade, Emilie; Jouin, Jenny; Colas, Maggy; Geffroy, Pierre-Marie; Masson, Olivier; Thomas, Philippe; Kagomiya, Isao; Asaka, Toru; Fukuda, Koichiro; Slodczyk, Aneta; Colomban, Philippe
Abstract: Dense lanthanum silicate oxyapatite samples La9.33 + x (SiO4 )6 O2 + 3x/2 were exposed to high water pressure in autoclave, in order to study the effects of oxygen stoichiometry and treatment duration on the protonation of these materials. TG analyses showed that protonic species were successfully introduced into the bulk of the material, especially for La9.60 (SiO4 )6 O2.4 sample after 84 h of treatment at 550 °C under 40 bar water pressure. It was shown that the mass loss compares well with perovskite materials and increases when protonation time rises (0.66% above 600 °C for 408 h), with a time limit beyond which the microstructure is no more stable. Rietveld refinement and Raman spectroscopy studies confirmed some structural modifications which could be linked to the incorporation of protonic species. It was shown that autoclave treatment induced an increase of the cell volume related to an increase of the a and b lattice parameters (enlargement of the characteristic channels of oxyapatite).